Visita domiciliar do enfermeiro no suporte ao cuidado materno do recém-nascido prematuro e de baixo peso: estudo de caso - Oliveira, Ana Izaura Basso de (2022)
Home visits require nurses to plan and be willing to take care of the care process, which is admittedly a complex practice that expands as the needs of mothers of high-risk newborns stand out, standing out as an effective tool for significantly reducing problems. social and health issues and as a commitment to the scope of parenthood. The general objective of this work is to investigate the support given to mothers in the home care of preterm and/or low birth weight newborns based on a nurse's home visit and recommendation for the use of the kangaroo position. The specific objectives were: To describe the needs of mothers of premature newborns and/or low birth weight newborns regarding the adoption of the kangaroo position and child care after hospital discharge; Propose a guiding document for nurses' home visits to mothers of premature and/or low birth weight newborns after hospital discharge;; Analyze maternal self-efficacy in caring for preterm and/or low birth weight children; Compare maternal self-efficacy at hospital discharge and at the end of home visits; Elucidate the perception of mothers of children born prematurely and/or with low birth weight in receiving a home visit from a nurse with guidance on the use of the kangaroo position. A mixed integrative, quantitative and qualitative study was proposed, with a concomitant transformative approach based on the methodological strategy of Case Study. The case was the relationship established by the nurse and the mother of a high-risk newborn during the home visit. The development of home visits took place from August 2020 to August 2021 in a city in the interior of São Paulo, where eight mothers of borderline or moderately premature and/or low birth weight infants received home visits from nurses every fortnight. The cases were recorded using an audio device and fully transcribed for study and analysis, as well as field notes were taken by the visiting nurses both from the home visits and from the contacts made by the mothers through electronic messaging. The cases were analyzed in the light of Meleis' Theory of Transitions and the Conceptual Basis of Care proposed by Ayres. At the beginning and end of maternal follow-up, the instrument “Preterm Parenting & Self-efficacy Checklist – Brazilian version” was applied. It was possible to highlight the domains "Confidence", "Importance" and "Success", which showed a statistically significant increase, and it can be inferred that there is an influence of the nurse's support on the daily care practices performed by the mother in the home environment, promoting better reach to maternal self-efficacy in the cases studied. In the qualitative analysis, it was possible to reach seven thematic units that deal with the transitional process of the mother of the newborn at risk established since the beginning of the pregnancy, where dreams are built and the feelings that surround motherhood are perceived. Premature birth and returning home is surrounded by fears and insecurities, where physical care is considered central to the child's well-being and progressive to the establishment of bonds and new ways of acting. Against the backdrop of the pandemic caused by the Sars-CoV-2 virus, the anxieties and threats to health, especially for newborns at risk, brought an additional component of concern to mothers who took this moment as a challenge to care. The maternal report permeates the care for the child and extends to the need to find adaptation in the midst of the changes caused by the arrival of the new member, however, little is verbalized and visualized as a woman, in this initial phase of returning home, in which the dimension of her care is involved by the projection of her responsibility of becoming a mother. In the midst of care, the father represents a central, participatory figure who plays an affective and supportive role for the mother. The kangaroo position was timidly highlighted based on the recognition of the benefits of the practice and professional support for the discoveries resulting from this new experience. The trajectory of care reveals, through lived experience, a conception of the health network that, in a peculiar way, codifies the organizations and recovers a lack in the ways of offering health services. Care for the newborn should start during prenatal care, emphasizing the importance of longitudinality and the relevance of moments in which there are exchanges of knowledge common to the period and which mean that these mothers are not void of knowledge at the time of the birth of the newborn. son, seeing themselves as mothers. The nurse's home visit focused on recognizing the kangaroo position favored empathetic care practices with the needs arising from the transitions that mothers of high-risk newborns go through, not attributing to them obligations and ways of acting that disregard them but offering a contact that supports difficulties that change over time and with child growth. It was possible to observe, as limitations of the study, the difficulty of accepting participation in the research at home due to interference from the family, social noise, maintenance of privacy, demands of the mother related to household chores, childcare and the pandemic by Sars-CoV-2. Thinking about parenting is a pressing process for health professionals and institutions with projections to the reception and relational space when becoming a mother and advancing to affective dimensions that can only be built as these women build their autonomy and allow themselves to deeply penetrate the bond between mother and child.